DEVELOPMENT OF MEMBRANE BASED ON BACTERIAL NANOCELLULOSE FROM WASTE BANANA PEELS, CELLULOSE AND NANO SILICA FOR DESALINATION APPLICATIONS - Kristianto Sijabat, Edwin
Desalination is the process of obtaining clean water from water that has a high salt content such as seawater. The desalination method that is currently being developed is the desalination method using a membrane because it has several advantages such as separation from the membrane without the need for additional chemicals and very minimum energy required. The membrane can act as a very specific filter. Only molecules of a certain size can pass through the membrane, while the rest will be stuck on the membrane surface. Membrane technology is also simple, practical, and easy to do. However, membranes derived from inorganic materials that exist today have shortcomings, including high production costs, requiring high pressure during operation, membrane design that is rigid, fragile, and inflexible. The above shortcomings can be overcome by utilizing the advantages of nanocellulose materials. The nanocellulose in this study was obtained from abundant banana peel waste in Indonesia through a relatively inexpensive, simple, and environmentally friendly process using the fermentation of the bacterium Gluconacetobacter xylinus. Nanocellulose produced from the synthesis of banana peels is usually called bacterial nanocellulose or Bacterial Nano Cellulose (BNC). The novelty of this research is the development of a BNC-based flat sheet membrane from waste banana peels and nano-silica for seawater desalination applications that have never been done before. The membrane composites were successfully made from BNC banana peel, cellulose, and silica with 1% chitosan and operated at working pressures of 4 and 5 bar. The membrane is hydrophilic with the highest Tearing Index 7.47 (mNm2 / g) and the highest Tensile Index 49.85 (Nm / g) at the composition of T1 (BNC 60%, 20% microcellulose, 20% silica). The smallest Wet Tensile Index reduction was 64.34% on the composition of T3 '(BNC 40%, microcellulose 20%, silica 40%). The flux in the membrane with a microsilica composition is greater than that of nanosilica. The maximum flux in microsilica - T3 (BNC 40%, 20% microcellulose, 40% silica) was 9,375 × 103 L / m2h while the nanosilica at - T3 '(BNC 40%, 20% microcellulose, 40% nanosilica) was 4,412 × 103 L / m2h.Desalination is the process of obtaining clean water from water that has a high salt content such as seawater. The desalination method that is currently being developed is the desalination method using a membrane because it has several advantages such as separation from the membrane without the need for additional chemicals and very minimum energy required. The membrane can act as a very specific filter. Only molecules of a certain size can pass through the membrane, while the rest will be stuck on the membrane surface. Membrane technology is also simple, practical, and easy to do. However, membranes derived from inorganic materials that exist today have shortcomings, including high production costs, requiring high pressure during operation, membrane design that is rigid, fragile, and inflexible. The above shortcomings can be overcome by utilizing the advantages of nanocellulose materials. The nanocellulose in this study was obtained from abundant banana peel waste in Indonesia through a relatively inexpensive, simple, and environmentally friendly process using the fermentation of the bacterium Gluconacetobacter xylinus. Nanocellulose produced from the synthesis of banana peels is usually called bacterial nanocellulose or Bacterial Nano Cellulose (BNC). The novelty of this research is the development of a BNC-based flat sheet membrane from waste banana peels and nano-silica for seawater desalination applications that have never been done before. The membrane composites were successfully made from BNC banana peel, cellulose, and silica with 1% chitosan and operated at working pressures of 4 and 5 bar. The membrane is hydrophilic with the highest Tearing Index 7.47 (mNm2 / g) and the highest Tensile Index 49.85 (Nm / g) at the composition of T1 (BNC 60%, 20% microcellulose, 20% silica). The smallest Wet Tensile Index reduction was 64.34% on the composition of T3 '(BNC 40%, microcellulose 20%, silica 40%). The flux in the membrane with a microsilica composition is greater than that of nanosilica. The maximum flux in microsilica - T3 (BNC 40%, 20% microcellulose, 40% silica) was 9,375 × 103 L / m2h while the nanosilica at - T3 '(BNC 40%, 20% microcellulose, 40% nanosilica) was 4,412 × 103 L / m2h. The rejection of salts on the membrane with a nanosilica composition was greater than that of microscopy. The maximum salt rejection in nanosilica - T2 '(50% BNC, 20% microcellulose, 30% nanosilica) was 4.89% while the microsilica at - T2 (BNC 50%, 20% microcellulose, 30% nanosilica) was 3.91%. In the comparison of the dead end and Cross Flow methods, the salt rejection in the dead end method was greater. In the dead end method, the maximum is 2.95% on membrane B (BNC 70%, microcellulose 10%, nanosilica 20%). In the cross flow method, the maximum is 1.39% on membrane A (BNC 80%, microcellulose 10%, nanosilica 10%). The flux in the dead end method is greater. In the dead end method, the maximum is 14.2 × 103 L / m2h on membrane B (BNC 70%, microcellulose 10%, nanosilica 20%). In the Cross Flow method, the maximum obtained is 9.329 × 103 L / m2h on membrane A (BNC 80%, microcellulose 10%,, nanosilica 10%). The value of flux and salt rejection tends to decrease in the dead end method, while the cross flow method until the 5th minute indicates the minimum fouling occurs.